Microinfarcts, brain atrophy, and cognitive function: The Honolulu Asia Aging Study Autopsy Study - Launer, Lenore J.; Hughes, Timothy M.; White, Lon R. (Annals of neurology, 2011)
Objective: This study was untaken to investigate the association of micro brain infarcts (MBIs) with antemortem global cognitive function (CF), and whether brain weight (BW) and Alzheimer lesions (neurofibrillary tangles [NFTs] or neuritic plaques [NPs]) mediate the association. Methods: Subjects were 436 well‐characterized male decedents from the Honolulu Asia Aging Autopsy Study. Brain pathology was ascertained with standardized methods, CF was measured by the Cognitive Abilities Screening Instrument, and data were analyzed using formal mediation analyses, adjusted for age at death, time between last CF measure and death, education, and head size. Based on antemortem diagnoses, demented and nondemented subjects were examined together and separately. Results: In those with no dementia, MBIs were strongly associated with the last antemortem CF score; this was significantly mediated by BW, and not NFTs or NPs. In contrast, among those with an antemortem diagnosis of dementia, NFTs had the strongest associations with BW and with CF, and MBIs were modestly associated with CF. Interpretation: This suggests that microinfarct pathology is a significant and independent factor contributing to brain atrophy and cognitive impairment, particularly before dementia is clinically evident. The role of vascular damage as initiator, stimulator, or additive contributor to neurodegeneration may differ depending on when in the trajectory toward dementia the lesions develop. ANN NEUROL 2011